2005
DOI: 10.1115/1.2098809
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Turbulence on Wake Dispersion and Blade Row Interaction in an Axial Compressor

Abstract: The influence of free-stream turbulence on wake dispersion and boundary layer transition processes has been studied in a 1.5-stage axial compressor. An inlet grid was used to produce turbulence characteristics typical of an embedded stage in a multistage machine. The grid turbulence strongly enhanced the dispersion of inlet guide vane (IGV) wakes. This modified the interaction of IGV and rotor wakes, leading to a significant decrease in periodic unsteadiness experienced by the downstream stator. These observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Both stator wakes and flow separation observed in the interrow spacing are convected through the rotor passage, appearing not fully-mixed at the rotor exit. As the distance from the source has been increased, the frequency is reduced because the integral length scales are further enlarged [21]: the small-scale turbulence is progressively dissipated and only large scales associated to primary flow patterns are preserved [59]. At the hub, important flow separation (also reported in [36]) provokes a further decrease of the cut-off frequency, swept all along the circumferential coordinate with the angular displacement of the blade-to-blade gradients.…”
Section: On the Estimation Of Accurate Mesh Sizes To Solve Les Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both stator wakes and flow separation observed in the interrow spacing are convected through the rotor passage, appearing not fully-mixed at the rotor exit. As the distance from the source has been increased, the frequency is reduced because the integral length scales are further enlarged [21]: the small-scale turbulence is progressively dissipated and only large scales associated to primary flow patterns are preserved [59]. At the hub, important flow separation (also reported in [36]) provokes a further decrease of the cut-off frequency, swept all along the circumferential coordinate with the angular displacement of the blade-to-blade gradients.…”
Section: On the Estimation Of Accurate Mesh Sizes To Solve Les Modellingmentioning
confidence: 99%
“…On the other hand, non-deterministic scales are mainly composed by turbulent structures. Several authors have investigated the impact of turbulent structures on the boundary layer development [18][19][20], while others have addressed the effect of freestream turbulence on wake decay and interaction processes [21][22]. Typically, turbulence intensity is described with statistical schemes, after substracting the resolved structures (deterministic flow) from the instantaneous measurements using the phaselocked averaging technique [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of both bypass transition and separated flow transition was observed; however, the classical T-S wave-driven transition was not found to be significant. Both Halstead et al [14] and Henderson et al [15] discussed the effect of freestream turbulence intensity as present in a multi-stage environment on wake dispersion and how this can modify the levels of wake deficit and unsteadiness as seen by downstream blades. The latter emphasised the importance of studying blade clocking effects on transitional flow development in multistage machines and especially within embedded stages.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations on the wake were carried out by Korakianitis 11 and Henderson et al 12 It can be seen from these investigations that the IGV or upstream stator wake can produce variations in performance and flow of successive rotor and stator blade row. Tiedemann and Kost 10 found that impinging nozzle guide vane wakes on the downstream stator resulted in decreased periodic fluctuations and variation in stator incidence.…”
mentioning
confidence: 99%
“…Tiedemann and Kost 10 found that impinging nozzle guide vane wakes on the downstream stator resulted in decreased periodic fluctuations and variation in stator incidence. Further investigations on the wake were carried out by Korakianitis 11 and Henderson et al 12 It can be seen from these investigations that the IGV or upstream stator wake can produce variations in performance and flow of successive rotor and stator blade row. However, the complexity of the flow phenomena involved makes it difficult to draw general conclusion [13][14][15] which indicate the need of further studies.…”
mentioning
confidence: 99%